Investigation of Antibiotic Resistance and Biofilm Formation in Clinical Isolates of Klebsiella pneumoniae - Kiana Karimi; Omid Zarei; Parinaz Sedighi; Mohammad Taheri; Amin Doosti-Irani; Leili Shokoohizadeh (International Journal of Microbiology)
Aim. Klebsiella pneumoniae (K. pneumoniae) is an encapsulated Gram-negative bacterium that can lead to 14–20% of nosocomial infections. The ability of biofilm formation in this bacterium decreases the host immune response and antibiotic efficacy. This may impose a huge impact on patients and healthcare settings. This study aimed to evaluate the antibiotic resistance pattern and biofilm formation in K. pneumoniae strains isolated from two major Hamadan hospitals, west of Iran. Methods. A total of 83 K. pneumoniae strains were isolated from clinical samples of patients in different wards of Hamadan hospitals from September 2018 to March 2019. Determination of antimicrobial susceptibility was performed using the disk diffusion method. Biofilm formation was evaluated by the crystal violet method. Data were analyzed by the SPSS software and chi-square test. Results. The results showed that clinical samples included 18 urinary tract samples (22%), 6 wound samples (7%), 6 blood samples (7%), 17 tracheal tube aspiration samples (20%), 32 throat cultures (38%), 2 sputum samples (2.5%), and 2 abscess drain cultures (2.5%). High-level resistance to cefotaxime was detected in 92%, and all of isolates were susceptible to colistin. Biofilm formation was seen in 62 (75%) isolates. Strong biofilm formation was observed in 17 (20%) strains. A significant correlation was seen between biofilm formation and antibiotic resistance (P value <0.05). Conclusion. Our findings emphasize the need for proper diagnosis, control, and treatment of infections caused by K. pneumoniae especially in respiratory tract infections due to the strong biofilm formation and high antibiotic resistance in these strains.